TRANSFORMASI MATA PENCAHARIAN SEBAGAI UPAYA MENJAGA KESTABILAN EKONOMI RUMAHTANGGA MASYARAKAT DESA JIKUMERASA - Oppier, Hermi; B. Nikijuluw, Jeanne; T. Matitaputty, Izaac; Bugis, Muhammad; Hahury, Hendri Dony (Sodality: Jurnal Sosiologi Pedesaan, 2025)
The role of tourism in maintaining economic stability at the household and regional levels is significant. The pursuit of enhanced household income opportunities has prompted individuals to transition their livelihoods from traditional sectors, such as fisheries, agriculture, and trade, to the tourism sector. However, the tourism sector is characterized by inherent challenges, notably its seasonal nature. This is further compounded by a dearth of knowledge concerning the management of tourist attractions among relevant business actors. To obtain a comprehensive understanding of the livelihood transformation from agriculture, fisheries, and trade to tourism, this study employed a qualitative research method with a phenomenological approach. The study was conducted in Jikumerasa Village, Buru Regency, Maluku Province Indonesia, involving informants who had transitioned from agriculture, fisheries, and trade to tourism. A total of 11 individuals were interviewed, including farmers, traders, employees, and fishermen. To enhance the credibility of the findings, a triangulation technique was employed, involving the insights of the village head, community leaders, and the manager of the Baikolet Jikumerasa Beach tourist attraction. The results indicate that the transformation of rural community livelihoods to the tourism sector is a multifaceted process involving economic diversification, social capital development, and cultural preservation. The predominant challenge confronting rural households pertains to the stability of their household economy, particularly with respect to meeting the manifold and evolving needs of their members. For these reasons, the government are suggested to promote community involvement, allocate resources to infrastructure development, and encourage the adoption of sustainable practices. These measures, if implemented, have the potential to unlock the full economic potential of tourism, thereby fostering the development of a resilient and thriving rural economy. To this end, government intervention through programs and policies is imperative, encompassing management training, financing, and promotion, to ensure the economic stability of households and beach attractions is maintained over the long term.